Skrining Kesehatan di Posyandu Lansia di Griyo Wirokerten Indah Banguntapan Sebagai Upaya Pencegahan Penyakit Tidak Menular : - - Ubaidillah (Jurnal Pengabdian Masyarakat Permata Indonesia, 2025)
Non-communicable diseases (NCDs) are diseases that are not caused by bacterial infection and cannot be transmitted from one person to another. These diseases are chronic, develop slowly over a long period, and are often influenced by lifestyle, environmental, and genetic factors. Examples include heart disease, stroke, cancer, diabetes, and chronic obstructive pulmonary disease (COPD). Early detection of a disease is a crucial step in disease prevention and treatment. Early detection of a disease is a crucial step in disease prevention and treatment, or a testing procedure to identify potential health problems or disorders in an individual. Conducting screening tests for healthy individuals can be beneficial for early prevention and to determine the prognosis of a disease. Screening tests are also beneficial for the wider community if the identification leads to primary and secondary prevention, detecting disease risks and preventing further impacts of disease risks. Screening activities are provided selectively, aiming to detect disease risks using specific methods. The purpose of implementing screening activities is a primary preventive measure to determine the health condition of the community. This community service program aims to determine the health status of the elderly and the need for advanced health services. The community service program was implemented through blood pressure, blood sugar, cholesterol, and uric acid screenings, as well as counseling and education. The program took place in February 2025 at a routine event at the Integrated Service Post Ismoyo Seto Griyo Wirokerten Indah in Banguntapan Bantul, Yogyakarta,). Fifty-three participants attended the program. The health checks included anamnesis, medical history, lifestyle, and existing health management efforts. Additionally, simple laboratory tests (blood sugar, cholesterol, and uric acid) were performed.Keywords: Scabies, Detention House, Sarcoptes scabiei Keyword : Health Screening, Elderly Health Services, Griyo Wirokerten Indah